ANALISIS KEPEMIMPINAN KEPALA SEKOLAH, BUDAYA KERJA, DAN KOMITMEN KERJA PENGARUHNYA TERHADAP PROFESIONALISME GURU DI YAYASAN SATU ATAP JABAL NUUR DUWET – WATES – KEDIRI - Lataza, Wulansari (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
The purpose of this study was to determine the effect of Principal leadership, work culture, work commitment, and teacher professionalism at the Jabal Nuur Duwet One Roof Foundation - Wates - Kediri. This study is a quantitative study that shows a causal relationship where the sample in this study was 45 teachers. Data collection techniques in this study used a questionnaire / questionnaire technique, interview techniques, and observation techniques. The analysis technique used is descriptive statistical analysis using percentages, averages and standard deviations, and for inferential statistical analysis using multiple linear regression tests, F Tests, T Tests, the coefficient of determination determination. The results showed that the principal's leadership was in the very good category in terms of personality indicators, knowledge, understanding of vision and mission, and communication skills. Work culture is in both categories in terms of indicators of discipline, openness, mutual respect, and cooperation. Work commitment is in both categories in terms of indicators of affective commitment, continuous commitment, and normative commitment. Whereas teacher professionalism is in both categories in terms of pedagogical competency indicators, personality competencies, social competencies, professional competencies. Based on multiple linear regression analysis shows that there is a positive and significant influence between school principals' leadership, work culture, work commitment, and the professionalism of teachers in Jabal Nuur Duwet One Roof Foundation - Wates - Kediri.